Sufficient Conditions of Blow-up and Bound Estimations of Blow-up Time for a Parabolic Equation in Multi-Dimensional Space (Journal of Nonlinear Modeling and Analysis, 2024)
In this paper, we establish some sufficient conditions on the heat source function and the heat conduction function of the parabolic equation to guarantee that $u(x,t)$ blows up at finite time, and give upper and lower bounds of the blow-up time in multi-dimensional space.
Keywords: Sufficient conditions; blow-up; upper and lower bounds; multi-dimensional space.